2014
DOI: 10.1039/c4ra08265f
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of mechanical activation and sulfurization to recover copper from waste printed circuit boards

Abstract: This work proposed a synergistic route of mechanic activation and sulfurization to recover copper from waste printed circuit boards for the first time and take successful use of free radical theory in assessing the synergism mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…32,33 Also, the reduction of the particle size and the increase of the specic surface area enhance the metal leaching with the ball milling. In Ou's paper, 60 the average particle size dropped to around 10 mm aer 20 minutes' milling. These physical and chemical changes help to decrease activation energy in order to make metal extraction easier.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…32,33 Also, the reduction of the particle size and the increase of the specic surface area enhance the metal leaching with the ball milling. In Ou's paper, 60 the average particle size dropped to around 10 mm aer 20 minutes' milling. These physical and chemical changes help to decrease activation energy in order to make metal extraction easier.…”
Section: Discussionmentioning
confidence: 95%
“…Ou's work 60 provides another interesting alternative route. Second-hand resources are like synthetic materials, not natural minerals, so there exists a great difference between the states of metal being present in second-hand resources and in natural minerals.…”
Section: Discussionmentioning
confidence: 99%
“…In general, mechanochemical synthesis reduces the number of steps and saves time in the preparation of products ( Ou et al, 2015 ). The synthesis of CuS NPs in a laboratory mill in 10 s was described in ( Balaz et al, 2016 ), as well as many other works have reported the successful synthesis of CuS in a short time ( Wang et al, 2006 ; Wang and Tan, 2010 ; Ou and Li, 2014 ). On an industrial scale, 60 min of milling was necessary to produce 7,500 g of CuS in one batch using an industrial eccentric vibrating mill ( Achimovičová et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the extraction method used, pretreatment plays a crucial role in the overall recovery process since metallic parts of WPCBs often need to be separated from encasing them polymer or ceramic materials before the extraction . Milling or pulverization is one of the most effective and widespread methods of this kind, it was repeatedly used by the different researchers to achieve high metal extraction rates . A new technique applying organic solvents for separation of WPCB components was reported in a recent past by a few groups of researchers .…”
Section: Introductionmentioning
confidence: 99%